Obstetrics and gynecology chair of the SibSMU: 115 years of pedagogical, scientific and practical activity - I. D. Yevtushenko; S. A. Nekrylov; V. P. Bolotova; A. Sh. Makhmoutkhodzhaev (Бюллетень сибирской медицины)
History of establishment, development and current status of one of the oldest chairs of the Siberian State medical University, chair of obstetrics and gynecology which marks by celebration its 115th anniversary is presented in the article.